AIRBNB AND ECONOMY HOTELS IN METRO MANILA: A COMPARATIVE ANALYSIS - Mary Vida L. Tumbali; Eduardo G. Ong (International Journal of Accounting, Finance and Business, 2020)
AIRBNB is an online community marketplace center encouraging transient rentals running from shared housing to whole homes that have now contributed more than ten million overall appointments to the supposed sharing economy (Zervas et al., 2017). How and whether hotels are reacting to the competition involves debate. The goal of this paper was to find out the effect of Airbnb’s presence with regards to hotel occupancy rates. Secondary Data are from the Department of Tourism (DOT), Philippine Tourism Satellite and Accounts (PTSA), and AirDNA - a paid service tool intended for Airbnb researchers. The t-test was the statistical test used in this study. This research was endeavored to see whether Airbnb's existence has caused a disruptive effect on the economy hotel industry in the Philippine setting and if there is any competition between hotels and Airbnb. The outcome of the study revealed that the year 2007-2011 has the highest value concerning occupancy rates compared to the year 2013-2017. The results signified that Airbnb slightly disrupts the economy hotels for the year 2016-2017.